Analysis of chronic kidney disease patients by targeted next-generation sequencing identifies novel variants in kidney-related genes - Alaamery, Manal; Alghamdi, Jahad; Massadeh, Salam; Alsawaji, Mona; Aljawini, Nora; Albesher, Nour; Alghamdi, Bader; Almutairi, Mansour; Hejaili, Fayez; Alfadhel, Majid; Baz, Batoul; Almuzzaini, Bader; et al. (Frontiers in Genetics, 2022)
Despite the enormous economic and societal burden of chronic kidney disease (CKD), its pathogenesis remains elusive, impeding specific diagnosis and targeted therapy. Herein, we sought to elucidate the genetic causes of end-stage renal disease (ESRD) and identify genetic variants associated with CKD and related traits in the Saudi kidney disease patients. We applied a genetic testing approach using targeted next-generation sequencing gene panel including 104 genes causative or associated with CKD. A total of 1098 Saudi participants were recruited in the study, including 534 patients with ESRD and 564 healthy controls. The pre-validated NGS panel was utilized to screen for genetic variants, and then a statistical analysis was conducted to test for associations. The NGS panel revealed 7,225 variants in the 104 sequenced genes. Cases had significantly higher number of confirmed pathogenic variants as classified by ClinVar database compared to controls (i.e., individuals with at least one allele of a confirmed pathogenic variant that is associated with CKD; 279 (0.52) vs 258 (0.45); P-value = 0.03). A total of 13 genetic variants were found to be significantly associated with ESRD in PLCE1, CLCN5, ATP6V1B1, LAMB2, INVS, FRAS1, C5orf42, SLC12A3, COL4A6, SLC3A1, RET, WNK1, and BICC1, including four novel variants that were not previously reported in any other population. Further studies are necessary to validate these associations in a larger sample size and among individuals of different ethnic groups.